The cerebellar deep nuclei: a patch for rate codes? - Gilbert, Mike; Rasmussen, Anders (Frontiers in Neural Circuits, 2025)
Neural firing rates are thought to represent values which code information. There are drawbacks with using biophysical events to represent numbers. (1) Rate code (like any sequence) is inherently slow to read. (2) At short intervals, the code becomes unintelligible biophysical noise. (3) Transmission times. The vital contribution of the cerebellum to skilled execution and coordination of movements requires precision timing. We present a theory supported by modeling that the output cell group of the cerebellar network is a practical solution to timing problems. In this role, it converts irregularly-patterned firing of Purkinje cells into an effectively instantaneous rate received by output cells, transforms the rate into linear analog modulation of output cell firing, synchronizes firing between output cells, and compensates for lag caused by extracerebellar transmission times. The cerebellum is widely connected to the midbrain and the cerebral cortex and involved in cognitive functions. Modular network wiring suggests that the cerebellum may perform the same computation on input from all sources regardless of where it is from. If so, and the deep cerebellar nuclei make the same contribution to the role of the cerebellum in other functions, an understanding of motor function would also provide insight into the substrate of cognitive functions.